Aplikasi Pembelajaran Bahasa Inggris Untuk Anak Usia Dini Berbasis Android - Oktaviani Oktaviani; Endah Kurniasari; Dheana Miralda (Pusat Riset dan Inovasi Nasional, 2023)
Interesting learning methods can increase children's interest in learning, especially young children. Learning methods using applications on computers, tablets and smartphones are starting to be created according to user needs. One of the Android-based applications that will be created is an English learning application for early childhood. This application consists of a main page which contains material choices, a material page which contains illustrated objects, and a quiz page which is a form of evaluation to train children's memory. The research method for making this application uses the System Development Life Cycle (SDLC). Starting with planning an overview of the application, analysis, design using Unified Modeling Language (UML), designing the application interface, to creating the application using Android Studio. Testing of the applications that have been created is carried out on several Android-based smartphone devices. The results achieved are that this Android application is able to function well and can be used as an English learning medium for young children.